Dilematisasi Pelajar sebagai Pengguna Sepeda Motor di Bawah Umur: Studi Kasus SMP Negeri 7 Palangka Raya - Rika; Rada Chiristina; Riska Priskilla; Rhema Y.R. Sanggew; Pita Lestari (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The purpose of this study is to narrate selected subjects in the search for multi-stakeholder responses (teachers, students, parents of students) for the use of underage motorcycles in the context of SMP Negeri 7 Palangka Raya. This research method uses qualitative research with descriptive research types. Sources of data in this study consisted of primary data sources, namely teachers and students at SMP Negeri 7 Palangka Raya. Secondary data sources consist of; books, research journals, websites and documentation that support this research. This data collection technique uses; observation, interviews with multi-stakeholder research subjects including Karkarmat, Rajungan, Jumaika, Irwanman, and Omiasi as well as documentation. This data analysis uses data reduction, data triangulation and conclusions. The results of the study indicate that there is a dilemma between regulatory praxis, violations, awareness of underage motorbike users, parents and teachers through various narratives as research outputs. The next researcher's recommendations are in the form of reprimands or sanctions given by the school for motorcycle users for junior high school students.